Jesus as Healer: Etymologizing of Proper Names in Luke-Acts - Reece, Steve (Zeitschrift für die neutestamentliche Wissenschaft, 2019)
The author of Luke-Acts embraces the time-honored literary tradition, both Hebrew and Greek, of attaching thematic significance to the etymologies of proper names. The fact that these are sometimes false etymologies based on a homophone in a different language - e. g., the festival name Pascha = "suffering," the place name Gaza = "treasure," the personal name Jesus = "healer" - is in accord with the methods of this etymological practice. Luke's false etymological association of the Hebrew name Jesus (Yeshua/Joshua - transliterated into Greek as Ἳησοῦς) with the Greek words for "healing" (ἴασις) and "to heal" (infinitive ἰῆσθαι), as bizarre as it may strike the modern philologist, serves as an implicit leitmotif that runs through the entirety of Luke-Acts (Luke 9,42; 14,3-4; 22,51; Acts 4,30; 9,34; 17,18).